Customer online purchase behavior on food delivery applications: a conceptual paper / Mohamad Haziq Izzuddin Baharin, Muhammad Izzat Zulkifly and Zurena@Rena Shahril - Baharin, Mohamad Haziq Izzuddin; Zulkifly, Muhammad Izzat; Shahril, Zurena@Rena (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
The tremendous development and demand in purchasing food products using cutting-edge technology can be plainly seen as Malaysia entered its endemic era. Nowadays, customers like to purchase food products in efficient and effective ways. As the popularity of Online Food Delivery (OFD) applications peaked, along with the rise in smartphone and internet use during the pandemic era, numerous compelling indications of unfortunate events, including inconsistent user experiences, unreliable delivery, and unacceptably wide price range, which negatively affects customer information satisfaction, intention, and purchasing behaviour. Thus, thorough investigation of customer online purchase behaviour on OFD applications is required. This study primarily reviews previous research on customer online purchase behavior on OFD Applications and aims to provide an in-depth understanding of the factors that influence the behavior, as well as customer information satisfaction, purchase intention and visibility through the lens of the Unified Theory of Acceptance and Use of Technology (UTAUT2). This study hypothesizes the new contributing construct of "trialability" and the growing moderating influence of "visibility" between customer information satisfaction and customer purchase intention of OFD applications usage. Furthermore, a major contribution of the customer information satisfaction construct to gauge real "information" satisfaction during application usage prior to purchase intention and actual purchase.